The True Relevance of Relevant Costs. - Dillon, Ray D.; Nash, John F. (The Accounting Review, 1978)
ABSTRACT: Relevant costing and incremental analysis are often-used decision-making tools. Irrelevant costs are excluded from any incremental decision-making problem because they are supposed to have equal effects on all the available alternatives. This paper demonstrates that when utility analysis is introduced, and when uncertainty exists, the "irrelevant" items may become relevant as the decision-maker's perspective shifts along his preference function. This phenomenon is especially true when large dollar "irrelevant" items prevail. The problem is further compounded when deciding the proper datum for the utility function and for the various costs and revenues.